2015
DOI: 10.1016/j.jcm.2015.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Stability of Resting Pulse Rates in Chiropractic Students

Abstract: Objective: This study assessed the short-term stability of resting pulse rate (RPR) over an approximate 10-minute period in college students. Methods: Thirty-one students were recruited as a convenience sample. The RPRs were manually measured in the seated position after 1, 3, 5, 7, and 9 minutes of seated rest. The RPRs were compared by rest time in repeated-measures analysis of variance. Results: Mean RPR increased by 1.9 beats per minute (BPM) from 1 minute of pretest rest to the 3-minute measurement (P b .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Moreover, if the HCT test protocol is accomplished correctly, one would expect only small variations in heart rate from trial to trial, within any given individual. For example, Hart (2015a) found that, over a two minute period in a resting condition, changes in mean heart rate were on average only between 1.5 bpm and 1.9 bpm in healthy students (Hart, 2015b). In a situation like heartbeat counting that requires concentration and attention during discrete trials with intermittent resting pauses, rather greater variation in heart rate can be expected (e.g.…”
Section: Further Data Anomaliesmentioning
confidence: 99%
“…Moreover, if the HCT test protocol is accomplished correctly, one would expect only small variations in heart rate from trial to trial, within any given individual. For example, Hart (2015a) found that, over a two minute period in a resting condition, changes in mean heart rate were on average only between 1.5 bpm and 1.9 bpm in healthy students (Hart, 2015b). In a situation like heartbeat counting that requires concentration and attention during discrete trials with intermittent resting pauses, rather greater variation in heart rate can be expected (e.g.…”
Section: Further Data Anomaliesmentioning
confidence: 99%
“…Albeit, f c could be expected to fluctuate in a narrow range and hence, could be assumed to be constant. Besides HR remains fairly stable or at worst fluctuates in a narrow range while resting, which indicates that f c fluctuates in a narrow range while resting (28). In the absence of a 'mathematical model' for f c , making this assumption simplifies calculation with minimal compromise with accuracy.…”
Section: Central Input-mentioning
confidence: 99%